2013
DOI: 10.1161/circulationaha.112.001254
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Signatures in Thrombus Aspirates of Patients With Myocardial Infarction

Abstract: Background-Infectious agents, especially bacteria and their components originating from the oral cavity or respiratory tract, have been suggested to contribute to inflammation in the coronary plaque, leading to rupture and the subsequent development of coronary thrombus. We aimed to measure bacterial DNA in thrombus aspirates of patients with STsegment-elevation myocardial infarction and to check for a possible association between bacteria findings and oral pathology in the same cohort. Methods and Results-Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 46 publications
(41 reference statements)
5
95
0
1
Order By: Relevance
“…We chose 8 target species (Streptococcus species, mainly Streptococcus mitis group, Staphylococcus aureus, Staphylococcus epidermidis, Prevotella intermedia, Fusobacterium nucleatum, Aggregatibacter [née Actinobacillus] actinomycetemcomitans, Dialister pneumosintes, Porphyromonas gingivalis, and Parvimonas micra), yielding the highest copy number levels in CLS aspirates of a most recent study, 16 including their oligonucleotide primers and probes. The detection limit was 40 cycles.…”
Section: Microbial Community Profilingmentioning
confidence: 99%
“…We chose 8 target species (Streptococcus species, mainly Streptococcus mitis group, Staphylococcus aureus, Staphylococcus epidermidis, Prevotella intermedia, Fusobacterium nucleatum, Aggregatibacter [née Actinobacillus] actinomycetemcomitans, Dialister pneumosintes, Porphyromonas gingivalis, and Parvimonas micra), yielding the highest copy number levels in CLS aspirates of a most recent study, 16 including their oligonucleotide primers and probes. The detection limit was 40 cycles.…”
Section: Microbial Community Profilingmentioning
confidence: 99%
“…Another potential pathogenic pathway is spillover of inflammatory mediators from periodontal tissues to the circulation during such everyday oral procedures [40]. Notably, both viable oral bacteria and DNA from oral bacteria have been isolated in atheromatous plaques distant from the oral cavity [4446]. Concomitant changes in endothelial permeability promote the entry and retention of cholesterol-containing low-density lipoprotein particles in the artery wall, which may aggravate atherosclerotic lesions and thus the risk of cardiovascular events [47].…”
Section: Discussionmentioning
confidence: 99%
“…Oral viridans streptococci was measured in 78% of thrombi and periodontal pathogens in 35%. 1 Furthermore, there was a significant association between the presence of periapical abscess and endodontic bacteria in the thrombus aspirates (odds ratio, 7.71) in 30 patients with available dental panoramic tomography. This is an exciting finding that begs the question of how the presence of a chronic oral infection can mediate an acute transition to plaque thrombosis.…”
Section: To the Editormentioning
confidence: 97%
“…Pessi et al 1 showed in 101 cases of ST-segment elevation myocardial infarction that bacterial DNA typical for endodontic infection was 16 times higher in thrombi than that found in patients' blood samples. Oral viridans streptococci was measured in 78% of thrombi and periodontal pathogens in 35%.…”
Section: To the Editormentioning
confidence: 98%